Effect of Clinical Trial Participation on Costs to Payers in Metastatic Non–Small-Cell Lung Cancer. Issue 8 (August 2021) - Merkhofer, Cristina; Chennupati, Shasank; Sun, Qin; Eaton, Keith D.; Martins, Renato G.; Ramsey, Scott D.; Goulart, Bernardo H. L.
Abstract : PURPOSE: The costs associated with clinical trial enrollment remain uncertain. We hypothesized that trial participation is associated with decreased total direct medical costs to health care payers in metastatic non–small-cell lung cancer. METHODS: In this retrospective cohort study, we linked clinical data from electronic medical records to sociodemographic data from a cancer registry and claims data from Medicare and two private insurance plans. We used a difference-in-difference analysis to estimate mean per patient per month total direct medical costs for patients enrolled on a second-line (2L) trial versus patients receiving standard-of-care 2L systemic therapy. RESULTS: Among 70 eligible patients, the difference-in-difference of mean per patient per month total direct medical costs between 2L trial participants and nonparticipants was –$6, 663 ( P = .01), for a mean savings of $45, 308 per patient for the duration of 2L trial therapy. In a secondary analysis by primary insurance payer, this difference-in-difference was –$5, 526 ( P = .26) for patients with commercial insurance and –$7, 432 ( P = .01) for patients with Medicare. CONCLUSION: Participation in a 2L trial was associated with a $6, 663 per month cost savings to health care payers for the duration of trial participation. Further studies are necessary to elucidate differences in cost savings from trial participation for Medicare and commercial payers. If confirmed, these results support health care payer investment in programs to improve clinical trial access and enrollment.